Comparing the effectiveness of concept-based curricula and video-based curricula in ESL primary classrooms - AMER, HEBA (2022)
Various countries around the world have benefited greatly from the technological advancements in the education sector. Modern technologies provide teachers the ability to set up new capabilities that can support not only their subject areas, but also various aspects of education. In the past, the use of video was just for entertainment and the teacher used to play videos that had nothing to do with educational content, and this is known as negative consumption. Currently, the video has become the teacher’s partner in explaining lessons and curricula through a reliable, effective, and attractive technology that makes lessons successful and allows students to comprehend the information more easily. The purpose of this research is to examine how digital videos can be used in education and to measure the effectiveness of digital videos on students from the perspective of teachers as technical integrators. Twenty classroom observations were conducted in grade 5 classrooms to examine the effectiveness of concept-based compared to video-based learning for teaching English grammar. Additionally, eighteen English teachers were interviewed in semi-structured interviews as part of the research. Methods and Procedures: In grade 5 classrooms, twenty observations were carried out and eighteen teachers were interviewed to determine what impact video-based curriculum applications had on the English primary classroom while studying English grammar lessons and how teachers viewed video-based curricula in comparison to content-based curricula. Outcomes: The findings from this study demonstrate that the students who studied using video-based learning as a learning approach, accompanied by discussion, performed significantly better than those who studied with concept-based learning in understanding English language grammar. In light of these findings, using video in the classroom is recommended for providing information to students in an easy and innovative manner.